Peran Aparatur Kecamatan Medan Timur Kota Medan Dalam Pembauatan E-KTP Pada Tahun 2019 - Elisabella Elisabella; Abdul Kadir; Yurial Arief Lubis (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2022)
The problem of E-KTP in Indonesia is a fairly large and complex problem, to date, various methods / approaches have been used by the government to tackle the e-KTP problem. As seen in the population administration services in the East Medan District Office related to the issuance of E-KTP. The problem that often occurs is the issue of E-KTP issuance due to the very limited E-KTP blank, lack of human resources in the implementation of E-KTP services. The purpose of this study was to determine the role of sub-district officials in the service of making / issuing E-KTP to the community and describing the constraints / obstacles in the service of making E-KTP. The research model used in this study is a descriptive method with a qualitative approach to data collection techniques, namely interviews, documentation, and observation (observation). The concept used in this study is the concept of Suhardono, (2018) reveals that the role in social science as a function that is brought by someone when occupying a position in a particular social structure. The function performed by a person in his social structure position is a set of behavior that is domiciled in the community, awareness and desire of the community to contribute in every government activity that implements policies and responds to the participation of the community as citizens. The results of this study indicate that the role of the District Apparatus in terms of service quality as well as the process undertaken in making the Identity Card (E-KTP) has been carried out well, only that there are deficiencies namely equipment facilities such as computers, printers and recording devices to facilitate filing in making e-KTPs and lacking the discipline of East Medan District Office staff so the process of making e-KTPs is rather slow and takes a long time.